2013
DOI: 10.1111/jopr.12061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Aging on Translucency of Resin‐Cemented Ceramic Veneers: An In Vitro Study

Abstract: The TP of the same color of resin cements varied related to the type or brand. Aging caused both the ceramics and cemented ceramics to become more opaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 32 publications
1
47
0
9
Order By: Relevance
“…Since the previous reports indicated that measuring quantitative color alterations by using CIE L ∗ a ∗ b with proper spectrophotometry and colorimetry techniques have several advantages such as repeatability, sensitivity, and objectivity, the spectrophotometry was used for calculating Δ E ∗ values for each material/pediatric drug in this study [25, 26, 29, 31]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the previous reports indicated that measuring quantitative color alterations by using CIE L ∗ a ∗ b with proper spectrophotometry and colorimetry techniques have several advantages such as repeatability, sensitivity, and objectivity, the spectrophotometry was used for calculating Δ E ∗ values for each material/pediatric drug in this study [25, 26, 29, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…L ∗ color coordinate represents lightness or brightness, a ∗ represents greenness (positive) and redness (negative), and b ∗ represents yellowness (positive) and blueness (negative). Numeric description of color permits precise definition of the magnitude of the color difference between objects [28, 29]. The color difference indicates whether a change in overall shade can be perceived by a human observer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentistry faces the challenge of quantifying, predicting, and controlling the color changes inherent to treatment with laminate veneers. Most investigators studying this topic (Öztürk et al ; Turgut and Bagis ; Turgut et al ) have computed color changes by means of electronic devices using the CIELAB system, owing to its international standardization and its objectivity. Nevertheless, the color coordinates (CIELAB system) form part of a language with which most dentists are not familiar.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that the color of the aesthetic materials remains stable over a long period in the oral environment [3][4] . Previous studies have described color changes occurring in direct dental composites [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%